Dietary polyunsaturated fatty acids effect on cecal microbiome profile of maturing broiler chicken - Vidya V. Jadhav; Yewande O. Fasina; Scott H. Harrison (Poultry Science)
Diet has been reported to impact the diversity and function of gut microbiota. Our study investigated the effect of dietary fat types on cecal microbial composition and predicted function in broiler chickens at days 41 and 55 of age. Four dietary fat sources were evaluated and compared to a control dietary fat source of poultry fat. These were for two diets rich in omega-3 polyunsaturated fatty acids (PUFA) - fish oil and flaxseed oil, a diet rich in long-chain saturated fatty acid (SFA) - lard, and a diet rich in medium-chain saturated fatty acid - coconut oil. At day 55, broiler chickens fed a PUFA-rich diet maintained cecal microbial diversity while broiler chickens fed a SFA-rich diet exhibited a significant reduction in diversity compared to the control diet-fed chickens. More specifically, PUFA intake was associated with elevated levels of microbial carbohydrate metabolizing capability, contributing to efficient energy utilization and enhanced short-chain fatty acid production capability. In contrast, SFA-rich diets lowered abundances for key microbial families like Lachnospiraceae and Bifidobacteriaceae hampering nutrient digestibility and pathogen resistance. The microbiomes for chickens fed lard and coconut oil diets showed a significant reduction in SCFA-producing microbial taxa abundance while the microbial functional profile indicated reduced carbohydrate metabolism. Our findings underscore the contrasting effects of SFA-rich fat and PUFA-rich fat on the cecal microbiota of broiler chickens. The results suggest that incorporating PUFA-rich dietary fats into broiler feed may offer potential benefits by modulating the cecal gut microbiota toward outcomes associated with elevated carbohydrate utilization without hampering nutrient digestibility and pathogen resistance.